C-Arm CT Measurement of Cerebral Blood Volume: An Experimental Study in Canines - Ahmed, A.S. (AJNR Am J Neuroradiol, 2009)
BACKGROUND AND PURPOSE: Cerebral blood volume (CBV) is an important parameter in estimating the viability of brain tissue following an ischemic event. We tested the hypothesis that C-arm CT measurements of CBV would correlate well with those made with perfusion CT (PCT). MATERIALS AND METHODS: CBV was measured in 12 canines by using PCT and C-arm CT. Two measurements with each technique were made on each animal; a different injection protocol was used for each of these techniques. PCT was performed by using a 64-section V-scanner. C-arm CT was performed by using a biplane Artis dBA system. PCT images were transferred to a commercially available workstation for postprocessing and analysis; C-arm CT images were transferred to a commercially available workstation for postprocessing and analysis by using prototype software. From each animal, 2 sections from each technique were selected for analysis. RESULTS: There was good agreement of both the color maps and absolute numbers between the 2 techniques. The maximum and mean deviations of values between the 2 techniques for the first 5 animals were 30.20% and 7.82%; for the second 7 animals, these values were 26.79% and 7.40%. The maximum and mean deviations between the 2 C-arm CT studies performed on the first 5 animals were 33.15% and 12.24%; for the second 7 animals, these values were 41.15% and 10.89%. CONCLUSIONS: In these healthy animals, measurement of CBV with C-arm CT compared well with measurements made with PCT.